The revelation of God: How and to whom does God reveals God self to? - H. Mdingi (Acta Theologica)
The African world view is not monolithic or homogeneous. However, that being the case, there is a strong metaphysical and existential leaning in terms of Spirit and the world. The Spirit is the medium whereby revelation occurs for all of creation. African indigenous knowledge as episteme and Black liberation theology as a paradigm have something to teach outside Western dualism about the revelation of God not being linear in form. The methodological aspect of this research is a literature study aimed at discussing transmission and reception of biblical discourse in Africa by viewing differently the subject of God’s revelation from a variety of sources. The article seeks to argue that indigenous knowledge and, from the Black liberation paradigm, conceptions of God reveal a God with a social existence in contrast to a Western God who abdicates creation when the majority of creation and her creatures are oppressed by White supremacy.